2016
DOI: 10.1179/2045772314y.0000000288
|View full text |Cite
|
Sign up to set email alerts
|

Low testosterone and non-alcoholic fatty liver disease: Evidence for their independent association in men with chronic spinal cord injury

Abstract: Objective: Non-alcoholic fatty liver disease (NAFLD) has been claimed as a liver phenotype of metabolic syndrome, which in turn is associated with male hypogonadism. We assessed whether an independent association between NAFLD and androgen deficiency could be revealed in men with chronic spinal cord injury (SCI), who exhibit a high prevalence of biochemical androgen deficiency and a combination of risk factors for metabolic syndrome. Design: Fifty-five consecutive men with chronic SCI admitted to a rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 42 publications
5
42
0
1
Order By: Relevance
“…[44] One blood sample was taken to measure total testosterone levels by chemiluminescence immunoassay, while NAFLD was diagnosed by abdominal US. Twenty-seven out of the 55 patients were diagnosed with NAFLD; all had a higher body mass index (BMI), insulin resistance (HOMA-IR), triglyceride levels, and GGT values, and lower total testosterone and FT levels.…”
Section: Laboratory and Clinical Evidence Showing Association Of Testmentioning
confidence: 99%
“…[44] One blood sample was taken to measure total testosterone levels by chemiluminescence immunoassay, while NAFLD was diagnosed by abdominal US. Twenty-seven out of the 55 patients were diagnosed with NAFLD; all had a higher body mass index (BMI), insulin resistance (HOMA-IR), triglyceride levels, and GGT values, and lower total testosterone and FT levels.…”
Section: Laboratory and Clinical Evidence Showing Association Of Testmentioning
confidence: 99%
“…22 Furthermore, 1 study reported that parenteral administration of testosterone to increase serum testosterone concentrations to within the normal range led to normalization of ALT levels. 23 Circulating androgen is known to be associated with a genderspecific risk of metabolic complications or NAFLD; associations of low serum testosterone levels with obesity, metabolic syndrome, and NAFLD have been well established in men, 6,7 but studies have suggested that increased androgenicity in healthy post-menopausal women was associated with an unfavourable cardiovascular risk profile. 24,25 In our study, a low serum testosterone level was associated with an increased risk for suspected NAFLD in men, but post-menopausal women with low serum androgen levels were also more prone to developing NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing data support the association between NAFLD and serum testosterone levels. [6][7][8][9][10] Several cross-sectional studies have reported a relatively consistent relationship between low total testosterone levels and NAFLD in men. 6,7 In women, data from the Multi-Ethnic Study of Atherosclerosis (MESA) indicated that post-menopausal women with fatty livers had higher serum total testosterone levels than those without fatty livers, which differed from the results of another study from Greece.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Obstructive sleep apnea syndrome (OSAS) is strongly associated with NAFLD independently of other traditional factors; it is a consequence of the decrease in the lipid metabolism provoked by intermittent hypoxia [182][183][184][185]. Other described diseases associated with NAFLD include osteoporosis [186], psoriasis [187], polycystic syndrome [188] and other endocrinopathies such as hypothyroidism [189], hypopituitarism [190] and hypogonadism [191]. Until now, there is no evidence for screening of all these pathologies for the mere fact that the subject presents NAFLD, so all that needs to be studied is the presence of them if the patient has clinical manifestations related to them.…”
Section: Other Associated Diseasesmentioning
confidence: 99%